A Multi-Informant Approach Testing an Expanded Home Numeracy Mode - Paola Bonifacci; Diego Compiani; Viola Ravaldini; Benedetta Peri; Alexandra Affranti; Valentina Tobia (MDPI AG, 2023)
The role of home numeracy activities in the development of numeracy skills is receiving growing interest, although some mixed results highlight the need to consider models that include different contextual variables. The present study was aimed at investigating, using a multi-method and multi-informant approach, how parents' educational levels, parents' numerical attitudes, home numeracy, and expectations toward their offspring's numeracy attitudes concurrently predict children's early numeracy abilities as measured with early numeracy tasks and through teachers' evaluations. The sample includes 430 preschoolers, their parents, and 56 teachers. The children's early numeracy competence was assessed using digit recognition and digit-quantity association tasks and via a proxy-report questionnaire administered to their teachers. The parents were then administered a questionnaire investigating their educational levels, home numeracy activities, math attitudes, and expectations toward their child's numeracy ability. The results of the structural equation models revealed that both children's performance in numeracy tasks and the teachers' evaluation of their math skills were directly predicted by their parents' educational levels. In contrast, the parents' math attitudes were indirect predictors via the mediation of home numeracy. These results contribute to understanding the relationships between the investigated environmental variables and the children's early math skills. Additionally, the implications for early family-based interventions are discussed.